2017
DOI: 10.18632/oncotarget.17590
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase-1 overexpression indicates poor prognosis in urothelial carcinoma of the urinary bladder and upper tract

Abstract: Urothelial carcinoma (UC), arising from the urothelium of the urinary tract, can occur in the upper (UTUC) and the urinary bladder (UBUC). A representative molecular aberration for UC characteristics and prognosis remains unclear. Data mining of Gene Expression Omnibus focusing on UBUC, we identified sulfatase-1 (SULF1) upregulation is associated with UC progression. SULF1 controls the sulfation status of heparan sulfate proteoglycans and plays a role in tumor growth and metastasis, while its role is unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The other upregulated genes in the top-10 for all three organoids were CYP3A4 (a key enzyme for drug metabolism), the serine protease PRSS33 , AC008555.1 , AC008555.2 , and SULF1 . SULF1 is a multitask protein with roles at the plasma membrane and cell nucleus that has both tumor suppressor and promotor actions [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other upregulated genes in the top-10 for all three organoids were CYP3A4 (a key enzyme for drug metabolism), the serine protease PRSS33 , AC008555.1 , AC008555.2 , and SULF1 . SULF1 is a multitask protein with roles at the plasma membrane and cell nucleus that has both tumor suppressor and promotor actions [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, while the accumulation of perlecan initially functions as a tissue barrier to slow metastatic spread [50], it simultaneously increases the availability of heparan sulfate chains that stabilize factors that can enhance tumorigenicity. Similarly, even though silencing of SULF1 has been mostly associated with poor prognosis in a variety of carcinomas [33,[51][52][53], we hypothesize that these outcomes rely heavily on the signaling context, such as type of tumor, disease stage, spatial distribution of GAGases, specific ligands, and other factors [32]. In fact, SULF1 has displayed tumor-promoting activity in pancreatic, urothelial, and gastric cancers [51,54,55], which further highlights the complex outcomes of SULF1 activity in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…For example, while the accumulation of perlecan 201 initially functions as a tissue barrier to slow metastatic spread [48], it simultaneously 202 increases the availability of heparan sulfate chains that stabilize factors that can 203 enhance tumorigenicity. Similarly, even though silencing of SULF1 has been mostly 204 associated with poor prognosis in a variety of carcinomas [31,[49][50][51], we hypothesize 205 that these outcomes rely heavily on the signaling context, such as type of tumor, disease 206 stage, spatial distribution of GAGases, specific ligands, and other factors [30]. In fact, 207 SULF1 has displayed tumor-promoting activity in pancreatic, urothelial, and gastric 208 cancers [49,52,53], which further highlights the complex outcomes of SULF1 activity in 209 vivo.…”
mentioning
confidence: 99%
“…stroma of primary prostate tumors[15], its cellular source(s) remained undetermined 48. In this study, we identified the cells that produce perlecan and its major enzyme49 modifier SULF1 and their respective roles in regulating Wnt3A-induced growth of50 metastatic PCa cells growing in perlecan-rich desmoplastic stroma, such as would occur 51 at sites of bone metastasis 52. February 26, 2020 2/21…”
mentioning
confidence: 99%